If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 0.7x + -3.6 Reorder the terms: y = -3.6 + 0.7x Solving y = -3.6 + 0.7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -3.6 + 0.7x
| 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 | | 2(y+5)-4y=16 | | 3n-n+5= | | 5+2(2x-5)=-2+3(x-2) | | 2x-5x=-1-5 | | -4x-8=3x-17 | | 750+30x=y | | -9(a+6)=2 | | y=-3.3x-3.3 | | x+x+11=37 | | 2(2x+1)+x=-39 | | y=-2x^2-24x-20 | | -9=m-98 | | Y^2+21y=0 | | 13=-7+r | | 4x-35=25 | | -1(x+3)=2x-12 |